« Deux épisodes dans la vie » de Gérald Godin : à la jonction du récit, du reportage et du journal de bord - Jonathan Livernois; Emmanuelle Germain (Contextes)
Two events, in 1970 and 1976, changed Gérald Godin’s life : he spent a week in Parthenais Jail (Montreal) during October Crisis 1970 and he became a Member of Parliament (National Assembly, Quebec) in 1976. In both cases, when he recounts the trauma and the exaltation of victory, he chooses to tell the story in a way between the personal diary’s writing and the newspaper report. Two works show this : "Journal d’un prisonnier de guerre" (Québec-Presse, November 1st, 1970) and "Journal d’une campagne électorale" (Possibles, Winter 1977). We want to delve deeper into the idea that Godin’s writings have a stabilizing virtue acting on the events, allowing him to represent them and represent them to others. His way of structuring his idea, of "fictionalizing the real", allows "to propose a mode of representation immediately comprehensible and accepted by all" (Marie-Ève ​​Thérenty). We also want to underline the fact that these Godin’s writings, which combine the journalist’s search of the truth and the unveiling in the diary, create a certain authenticity in line with his conception of literature and politics.